Katalog Jiwani - Rivandra Asrina Dinata; Budiwirman Budiwirman (Departement of Mathematics Education, 2023)
Jiwani is a cafe located on Jl. Behind Olo 1 No. 20, Padang City. Jiwani was founded in 2021, its founder is Sayyid Syauqi Alva. Jiwani already has an information medium in the form of Instagram but there are still many obstacles such as unclear product information and the use of promotional Instagram media, making this media have many limitations in providing detailed product information. the author aims to design media information that is useful, interesting and informative to provide information on the products to be sold. The design method used is the glass box method with SWOT analysis techniques. This design uses a simple and minimalist concept, where this style will make the information to be conveyed clear and simple so that it is easy to understand. The results of this media design are in the form of a physical book catalog which will provide information about what Jiwani and its products are, also accompanied by other supporting media such as posters, business cards, x-banners, and id cards.